Determination of field distortion of astronomical telescopes by means of the simultaneous adjustment method - Stock Leyton, Maria Jeanette; Stock, Jurgen; Patnaik, Ras (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
There are three ways to determine the field distortion produced by astronomical telescopes: a) the direct comparison of measured coordinates with theoretical coordinates derived of an astrometrical catalog of high precision: b) the analysis of the residuals obtained from the linear reduction of a set of plates as a function of the coordinates in an area which correspond to the size of the plates and c) the a priori application of a series of tentative corrections based on a mathematical model of the distortion in the form of a polynomial, determining empirically the parameters which gives the best adjustment. This last process is considerably strengthened by the simultaneous adjustment of a set of plates with adequate overIap. This work proves the correct performing of the last method by a numerical simulation.